2011
DOI: 10.1167/iovs.11-7557
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Retardation Patterns in Scanning Laser Polarimetry Are Associated with Low Peripapillary Choroidal Thickness

Abstract: Low values of TSS resulting from the appearance of ARP in SLP are associated with low peripapillary choroidal thickness. Reduced choroidal thickness may result in an increased amount of confounding light getting to the SLP light detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Although it may also be the case that the choroid is thicker in Korean eyes, Chung et al33 measured PCT using Spectralis circle scans in 87 healthy Korean eyes and reported an average thickness of 157.3 μm, which is within the confidence intervals of our measurements at 900 and 1000 μm (roughly the position of a standard circle scan within our data). Several other studies have reported global PCT within standard 12° (or 3.4 mm diameter) circle scans in a wide variety of healthy participants that varies from 130 μm to 167 μm,3442 which are again within the confidence intervals of our measurements at the PCT-900 μm and PCT-1000 μm measurement points.…”
Section: Discussionsupporting
confidence: 87%
“…Although it may also be the case that the choroid is thicker in Korean eyes, Chung et al33 measured PCT using Spectralis circle scans in 87 healthy Korean eyes and reported an average thickness of 157.3 μm, which is within the confidence intervals of our measurements at 900 and 1000 μm (roughly the position of a standard circle scan within our data). Several other studies have reported global PCT within standard 12° (or 3.4 mm diameter) circle scans in a wide variety of healthy participants that varies from 130 μm to 167 μm,3442 which are again within the confidence intervals of our measurements at the PCT-900 μm and PCT-1000 μm measurement points.…”
Section: Discussionsupporting
confidence: 87%
“…It was shown that these artifacts occur in eyes that provide a deep penetration of the sampling beam into the birefringent sclera, 23 an effect likely related to a thin choroid. 24 SLP has no depth segmentation capability and, therefore, the origin of the birefringence cannot be localized. Although recently the enhanced cornea compensation (ECC) version of the SLP has reduced these artifacts, 21,25 PS-OCT can overcome this limitation completely because it provides depth resolved information.…”
mentioning
confidence: 99%